Discussion on two methods for determining static strength of tubular T-joints at elevated temperature. Issue 5 (May 2017) - Shao, Yongbo; Zhao, Haicheng; Yang, Dongping
To predict the static strength of a welded tubular joint at elevated temperature using finite element simulation, two methods in the literature were reported. The first method aims to analyze the static strength of a tubular joint at a specified elevated temperature, and a routine mechanical analysis is carried out by defining the material properties at the specified elevated temperature according to some specifications. This method does not consider the heat transfer process of the tubular joint in a fire condition. The second method is used to determine the static strength of a tubular joint using a combination of transient state heat transfer analysis and mechanical analysis. The tubular joint subjected to a specified load is heated in accordance with ISO 834-1 standard fire curve to fail at a critical temperature, and the specified load is considered as the static strength of the joint at the critical temperature. In this study, a detailed parametric study on the failure process of circular hollow section tubular T-joints at elevated temperature is carried out using finite element method. The static strengths of the circular hollow section T-joint models obtained from the two methods are compared. The comparison shows that the first method produces a higher estimation on the static strength compared to the second method. Finally, the effect of some geometrical parameters, chord stress ratio, and elevated temperature on the difference of the two methods is also investigated.